SPOOL VALVE FOR VEHICLE AND MANUFACTURING METHOD THEREOF - PARK EUNSIL (2019)
The present invention provides a spool valve for a vehicle and a manufacturing method thereof. According to the present invention, the spool valve for a vehicle comprises: a spool body that is surface-treated for a porous surface to be formed; and a pigment layer painted on the porous surface to distinguish an installation position of the spool body. 차량용 스풀 밸브 및 그 제조방법에 대한 발명이 개시된다. 본 발명의 차량용 스풀 밸브는: 표면처리됨에 따라 다공성 표면이 형성되는 스풀 바디; 및 스풀 바디의 설치 위치를 구분할 수 있도록 다공성 표면에 착색되는 안료층을 포함하는 것을 특징으로 한다.